IMPLEMENTASI REST API PADA APLIKASI UNTUK PENCEGAHAN STUNTING DAN MONITORING KESEHATAN ANAK (MOANA) BERBASIS WEB - Asra, Tanzilla Nurdhia; Aji, Adam Sekti (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Stunting is a condition where infants are shorter in height than their peers, caused by poor parenting practices. This can negatively impact a child's health, increasing the risk of illness and even death. The current data collection system for monitoring child growth and development still relies on books, which are consIDered inefficient and prone to data loss due to damage or exposure to water. This research aims to improve data collection services by utilizing website technology for online and real-time data input. The hope is to provIDe convenience for users in inputting child growth and development data without the risk of losing data. In this study, the data collection process was carried out by means of interviews and direct observation of several posyandu and mothers of toddlers. This research produces a website-based application for admin or posyandu officers. With Visual Studio Code tool and MySQL database. In testing using the Black Box Testing method, the features of the application run quite well from several samples that have been tested. So, with this program tracking child growth and development can be done more effectively and efficiently.